1984
DOI: 10.1007/bf02014332
|View full text |Cite
|
Sign up to set email alerts
|

Six cases of acute appendicitis with secondary peritonitis caused byStreptococcus pneumoniae

Abstract: In six previously healthy children and adults with typical acute appendicitis, Streptococcus pneumoniae was isolated from peritoneal swabs or periappendicular pus in pure culture (four patients) or together with intestinal flora. Pneumococci recovered by abdominal paracentesis are not pathognomonic of socalled primary or spontaneous peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Information regarding previous respiratory infections was not available for all cases, but no patient questioned by this has reported previous infection [5][6][7][8][9], and only 1 presented pneumococcal nasopharynx colonization [7]. We have neither assessed the occurrence of previous infection nor previous administration of antipneumococcal vaccine.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Information regarding previous respiratory infections was not available for all cases, but no patient questioned by this has reported previous infection [5][6][7][8][9], and only 1 presented pneumococcal nasopharynx colonization [7]. We have neither assessed the occurrence of previous infection nor previous administration of antipneumococcal vaccine.…”
mentioning
confidence: 97%
“…It is intriguing, therefore, that only 1 case was associated with the expected enteric microorganisms [6,13]. In fact, in most cases (87.5%, 14/16), S pneumoniae was detected in pure cultures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some reports of pneumococcal peritonitis in patients with cirrhosis or nephrotic syndrome, in those undergoing continuous peritoneal dialysis, in bone marrow transplant patients, and in patients with rheumatoid arthritis or systemic lupus erythematosus [5,6]. Abdominal pneumococcal infections have also been described in patients with acute appendicitis [7]. In a recent review, pneumococcal peritonitis in previously healthy adults was associated with genital infections [5].…”
Section: Introductionmentioning
confidence: 97%
“…Intra-abdominal infections due to S. pneumoniae are rare; Heltberg et al [3] reported only six cases of primary pneumococcal appendicitis during the years 1967 to 1981 and S. pneumoniae was isolated only from one patient's peritoneal fluid out of 296 perforated appendicitis cases [2]. The mechanism of the appendix colonisation by the bacteria is either by mucosal translocation leading to direct invasion of gut wall or via haematogenous seeding [5].…”
mentioning
confidence: 95%